2017
DOI: 10.3390/su9081492
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Valorization and Application of Bio-Waste Derived Compounds from Potato, Tomato, Olive and Cereals: A Review

Abstract: Abstract:The vast and ever-growing amount of agricultural and food wastes has become a major concern throughout the whole world. Therefore, strategies for their processing and value-added reuse are needed to enable a sustainable utilization of feedstocks and reduce the environmental burden. By-products of potato, tomato, cereals and olive arise in significant amounts in European countries and are consequently of high relevance. Due to their composition with various beneficial ingredients, the waste products ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 362 publications
(420 reference statements)
0
102
0
3
Order By: Relevance
“…The results of this study by PLSR method show that the soil nutrient factors influencing potato quality from large to small were soil ammonium nitrogen > soil available phosphorus > soil nitrate nitrogen > available potassium > pH. The content of potato starch, vitamin C, soluble total sugar, potato crude protein, and reducing sugar can be significantly increased by applying appropriate nitrogen, phosphorus, and potassium fertilizer into potato planting plot [56]. In this study, the pH was significantly correlated with starch content, reducing sugar content, and soluble protein content.…”
Section: Discussionmentioning
confidence: 81%
“…The results of this study by PLSR method show that the soil nutrient factors influencing potato quality from large to small were soil ammonium nitrogen > soil available phosphorus > soil nitrate nitrogen > available potassium > pH. The content of potato starch, vitamin C, soluble total sugar, potato crude protein, and reducing sugar can be significantly increased by applying appropriate nitrogen, phosphorus, and potassium fertilizer into potato planting plot [56]. In this study, the pH was significantly correlated with starch content, reducing sugar content, and soluble protein content.…”
Section: Discussionmentioning
confidence: 81%
“…Biological production of platform chemicals from agro-resources, biomass waste and food processing residues has been reported in the literature Sheldon, 2014;Lin et al, 2013;Dugmore et al, 2017;Fritsch et al, 2017). However, valorisation techniques have only been validated at lab-scale.…”
Section: Challenge Iii: Converting Agricultural Residues Into Innovatmentioning
confidence: 99%
“…Potato residues are generally considered a waste, and in most cases, they are discarded. As mentioned above, several researchers suggest that potato peel is a valuable source of bioactive compounds and nutrients, including antioxidants, dietary fibre, pigments, vitamins and minerals (Akyol et al , ; Fritsch et al , ; Priedniece et al , ; Pathak et al , ). Some approaches have recently proposed the valorisation of this waste through fermentation routes, which can provide industrial enzymes and biofuels as a promising source of energy (Galhano dos Santos et al , ; Gebrechristos & Chen, ).…”
Section: Valorisation Of Potato Wastes: a Biorefinery Approachmentioning
confidence: 99%
“…Researchers have shown that potato processing wastes can be an important source of compounds such as proteins, starch, glycoalkaloids (Priedniece et al , ; Gebrechristos & Chen, ), dietary fibre (Schieber & Saldaña, ; Scharf et al , ) and phenolic compounds (Singh & Saldaña, ; Singh et al , , ; Wijngaard et al , ; Akyol et al , ; Kumari et al , ). Due to the valuable composition, biorefinery approaches using potato peel as biomass to convert it into an array of products by means of different paths and processing methods have been proposed (Ahokas et al , ; Fritsch et al , ; Pathak et al , ). To the best of our knowledge, however, those studies have been developed in several potato species different from the Group Phureja.…”
Section: Introductionmentioning
confidence: 99%